Method for recovering bisphenol A through polycarbonate hydrolysis

By mixing the polycarbonate material with bisphenol A monomer, alkali and water at room temperature and normal pressure without adding a catalyst, the hydrolysis reaction is solved, and the problem of using strong alkali and catalyst in the prior art is solved, achieving efficient recovery of bisphenol A and reducing costs.

CN119569539AActive Publication Date: 2025-03-07WANHUA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411661133.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art requires the use of a large amount of strong alkali and catalyst when recycling bisphenol A in waste polycarbonate, resulting in equipment corrosion, large amount of wastewater and inability to recycle the catalyst, and high temperature in the reaction conditions affect the stability of bisphenol A.

Method used

By using a method of mixing the polycarbonate material with bisphenol A monomer, alkali and water at room temperature and normal pressure, forming a uniform emulsion through shearing, and hydrolysis reaction is carried out to obtain an aqueous solution containing bisphenol A. The aqueous solution does not contain inorganic salt impurities, and is suitable for the synthesis of polycarbonate in the interfacial polycondensation method.

Benefits of technology

It realizes efficient recycling of bisphenol A under mild conditions, avoids the use of catalysts and strong alkalis, reduces equipment corrosion and wastewater, improves recycling efficiency, and enables the recovered aqueous bisphenol A solution to be directly used in the synthesis of polycarbonate, saving costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for recovering bisphenol A through polycarbonate hydrolysis. The method comprises the following steps: (1) dissolving a polycarbonate material in an organic solvent to obtain a solution X; (2) mixing a bisphenol A monomer, alkali and water to obtain a solution Y; (3) mixing the solution X and the solution Y, shearing to obtain a uniform emulsion, and transferring into a reactor for hydrolysis reaction; and (4) the reaction liquid is demulsified and separated to obtain a water phase and an oil phase, and the water phase is an aqueous solution containing bisphenol A. The aqueous solution containing bisphenol A obtained by the method can be directly used for synthesizing polycarbonate by an interface phosgene method, the remaining oil phase returns to the solution X after being distilled and concentrated and is mixed with the solution Y again to prepare an emulsion, and the hydrolysis rate of solid polycarbonate waste can reach more than 50% under the condition that the reaction system circulates for less than 5 times. The whole reaction process is carried out in a non-catalyst and non-high-temperature environment, the bisphenol A solution generated by hydrolysis can be directly applied to synthesis of polycarbonate, the material production cost is reduced, and considerable economical efficiency and environmental friendliness are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of extracting bisphenol A from waste polycarbonate, and particularly relates to a method for completing alkaline hydrolysis of polycarbonate material under mild conditions without adding a catalyst. Background Art

[0002] Polycarbonate (PC) materials have excellent impact resistance and good optical properties, which make them widely used in the construction industry, automobile industry, electronic appliances and other fields. As one of the three major engineering plastics, it has gradually become the top engineering plastic product in global consumption in recent years. However, the large-scale use of materials has also brought about the disposal problem of waste polycarbonate. The best solution for this type of material is to recover bisphenol A monomer in waste PC by alcoholysis.

[0003] For example, Liu Yaoyuan et al. (Plastics Science and Technology, 2014, 42(3):74-77) reported a method of using methanol to hydrolyze CD-grade PC to recover bisphenol A (BPA). Although this process can effectively degrade PC, it requires a large amount of strong alkali as a catalyst, which corrodes equipment, produces a large amount of wastewater, and the catalyst cannot be recycled. In addition, the alcoholysis process often reacts at high temperatures, and the increase in temperature will inevitably affect the stability of bisphenol A. In addition, the residue of small molecule alcohols will also have a certain impact on the application of bisphenol A in the synthesis of polycarbonate materials in the optical field.

[0004] Ionic liquids can also be used as catalysts and reaction media to catalyze the alcoholysis of waste PC methanol. This method overcomes the technical problem of consuming a large amount of high-concentration inorganic strong acid / base and not being able to reuse it. However, the synthesis steps of ionic liquids are cumbersome, costly, and require large amounts of use. Although ionic liquids are new green solvents, their greenness lies in their lack of obvious vapor pressure, good thermal stability, and safe operation. However, the synthesis, purification, and recovery processes of ionic liquids all use a large amount of volatile organic solvents. As catalysts or solvents, a portion of the ionic liquids will eventually be lost to the environment, which will have varying degrees of impact on the environment.

[0005] Therefore, it is of great significance to find a polycarbonate decomposition method with mild reaction conditions and less impurities to improve the shortcomings of the existing process and realize the chemical recycling of waste polycarbonate materials. Summary of the invention

[0006] In view of the above problems existing in the prior art, the object of the present invention is to provide a method for recovering bisphenol A by hydrolyzing polycarbonate (PC), wherein a PC polymer is hydrolyzed under mild conditions of room temperature, normal pressure / without a catalyst to obtain an aqueous solution containing bisphenol A, and the aqueous solution does not contain impurities such as inorganic salts, and can be directly used in the interfacial polycondensation method to synthesize polycarbonate.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] A method for recovering bisphenol A by hydrolyzing polycarbonate, the method comprising the following steps:

[0009] (1) dissolving a polycarbonate material in an organic solvent to obtain a solution X;

[0010] (2) mixing bisphenol A monomer, alkali, and water to obtain a solution Y;

[0011] (3) mixing solution X and solution Y, obtaining a uniform emulsion through shearing, and transferring the mixture into a reactor for hydrolysis reaction;

[0012] (4) The reaction liquid is demulsified and separated to obtain a water phase and an oil phase, respectively, wherein the water phase is an aqueous solution containing bisphenol A.

[0013] In one embodiment, the polycarbonate material in step (1) is selected from a polymer containing bisphenol A carbonate structural units in the molecular chain, preferably a polymer containing only bisphenol A carbonate structural units in the molecular chain; preferably, the molecular chain refers to the main chain;

[0014] In a preferred example, the average molecular weight of the polycarbonate material is 2000-40000 g / mol, including but not limited to 2000 g / mol, 5000 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, 35000 g / mol, 40000 g / mol or a range between any two thereof;

[0015] Specifically, the polycarbonate material may be a homopolymer having a bisphenol A carbonate repeating structural unit, or may be a copolymer containing a bisphenol A carbonate repeating structural unit, such as a copolymer derived from bisphenol A and optionally other one or more bisphenols / dihydroxy aromatic compounds (such as resorcinol), and further comprising one or more non-carbonate structural units such as aromatic ester units (such as terephthalic acid, isophthalic acid), aromatic-aliphatic ester units based on C6-20 aliphatic diacids, and polysiloxane units (such as polydimethylsiloxane units);

[0016] The polycarbonate material may be a linear polymer or a branched polymer, and may be a polycarbonate of a single structure or a combination of polycarbonates of multiple structures.

[0017] The specific source of the polycarbonate material applicable to the present method is not limited, and it can be new polycarbonate material or recycled polycarbonate material; specifically, the polycarbonate material can include but is not limited to virgin polycarbonate material, recycled polycarbonate generated by daily consumption, recycled polycarbonate generated by industrial production, etc. The polycarbonate material has no special requirements for its preparation method, and can be obtained from a variety of sources, and can include a combination of polycarbonates with slight structural differences. The differentiated structure can be a change in comonomers or end groups, for example, polycarbonates prepared by introducing various end-capping agents / chain terminators during polymerization.

[0018] It should be noted that when the raw material is recycled polycarbonate material, it may also contain one or more blended modified polymers such as thermoplastic polymers other than polycarbonate.

[0019] In one embodiment, in step (1), the polycarbonate material is dissolved in an organic solvent to obtain a solution X, wherein the mass percentage of the polycarbonate material in the solution X is 10-30%, including but not limited to 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% or a range between any two thereof.

[0020] In one embodiment, the organic solvent selected for dissolving in step (1) is a polar solvent, preferably a chlorine-containing organic solvent such as a halogenated hydrocarbon, more preferably one or more of dichloromethane, chlorobenzene, and the like.

[0021] In one embodiment, the dissolution process in step (1) may be appropriately heated. Specifically, the temperature of the dissolution process is controlled at 24-38°C, including but not limited to 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C, 38°C or a range between any two thereof; the temperature of the dissolved solution X obtained is controlled at 25-35°C, including but not limited to 25°C, 26°C, 28°C, 30°C, 32°C, 34°C, 35°C or a range between any two thereof.

[0022] In one embodiment, in step (1), a polycarbonate material is dissolved in an organic solvent. The polycarbonate material can be a powder / granule discarded from the production of the device, or a polycarbonate molding material sold on the market after use. When using powder / granule, especially a molded polycarbonate material as a raw material, the material needs to be crushed first. The crushing equipment available includes a grinder, a crusher, etc. In order to accelerate the dissolution, the diameter of the crushed granules should be as small as possible. Preferably, the diameter of the polycarbonate material after crushing should not exceed 1 mm, preferably 0.05-0.5 mm. Specifically, the diameter of the crushed particles includes but is not limited to 1 mm, 0.8 mm, 0.6 mm, 0.5 mm, 0.3 mm, 0.2 mm, 0.1 mm, 0.05 mm, 0.01 mm, or a range between any two of them.

[0023] In one embodiment, the solution X obtained after the polycarbonate material is dissolved in step (1) needs to be filtered, that is, the solution X passes through a filtering device before being transported backward; the filter material selected for filtration should have a pore size range of less than 10 μm, preferably 0.5-7 μm. Specifically, the pore size of the filter material includes but is not limited to 10 μm, 9 μm, 8 μm, 6 μm, 4 μm, 2 μm, 1 μm, 0.5 μm, 0.1 μm or a range between any two thereof; wherein the filter material is not limited, and can be an oleophilic material such as PTFE (polytetrafluoroethylene) and the like.

[0024] In one embodiment, in step (2), bisphenol A monomer, alkali and water are mixed to obtain solution Y, wherein solution Y is an alkaline aqueous solution containing bisphenol A monomer, wherein the mass percentage of bisphenol A monomer is 0.05-1.5%, and the mass percentage of alkali is 2-8%; specifically, the mass percentage of bisphenol A monomer includes but is not limited to 0.05%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or a range between any two thereof, and the mass percentage of alkali includes but is not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or a range between any two thereof;

[0025] In a preferred example, the solution Y is strongly alkaline, and its pH is 12-14, including but not limited to 12, 12.2, 12.5, 12.8, 13, 13.2, 13.5, 13.8, 14 or a range between any two thereof;

[0026] In a preferred example, the mixing in step (2) is carried out at room temperature, and the temperature of the solution Y obtained by mixing the raw materials is controlled at 25-35°C, including but not limited to 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C or a range between any two of them.

[0027] In one embodiment, the solution Y in step (2) contains a base to make it strongly alkaline, wherein the added base is an inorganic base, preferably a hydroxide; specifically, the hydroxide includes but is not limited to alkali metal hydroxides, alkaline earth metal hydroxides, tetraalkylammonium hydroxides, ammonium hydroxide, etc.;

[0028] In a preferred example, the base is selected from alkali metal hydroxides, such as one or more of NaOH, KOH, etc.;

[0029] In practical applications, the alkali may also be an aqueous alkali solution, such as an aqueous alkali solution with a concentration of 1-40wt%, but its amount is calculated based on the alkali contained therein. Specifically, the concentration of the aqueous alkali solution includes but is not limited to 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or a range between any two of them.

[0030] In one embodiment, the solution Y of step (2) further contains a certain amount of reducing agent, wherein the content of the reducing agent in the system is 50-500 ppm, including but not limited to 50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm, 400 ppm, 450 ppm, 500 ppm or a range between any two thereof;

[0031] Specifically, the reducing agent is selected from sodium or potassium sulfide, sulfite, etc., preferably sodium thiosulfate.

[0032] In one embodiment, when the solution X and the solution Y are mixed for shearing operation in step (3), it is necessary to perform the shearing operation in a certain ratio. Specifically, the mass ratio of the solution X to the solution Y is 0.5-5.0, preferably 0.5-2.0, including but not limited to 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5.0 or any range therebetween.

[0033] In one embodiment, after the solution X and the solution Y are mixed in step (3), the bisphenol A monomer contained in the solution Y can promote the formation of a uniform emulsion, and the solution X and the solution Y can be completely mixed to form a uniform and stable emulsion by high-speed shearing. Specifically, the linear speed range of the shearing is 2-20 m / s, including but not limited to 2 m / s, 5 m / s, 8 m / s, 10 m / s, 12 m / s, 14 m / s, 16 m / s, 18 m / s, 20 m / s or a range between any two thereof;

[0034] Preferably, the total shear power of the shear process system is controlled to be 0.5-3.0*10 6 J / m 3 , including but not limited to 0.5*10 6 J / m 3 , 0.8*10 6 J / m 3 , 1*10 6 J / m 3 , 1.2*10 6 J / m 3 , 1.5*10 6 J / m 3 , 1.8*10 6 J / m 3 , 2*10 6 J / m 3 , 2.2*10 6 J / m 3 , 2.5*10 6 J / m 3 , 2.8*10 6 J / m 3 , 3.0*10 6 J / m 3 Or the range between any two of them; the total shear power of the shear process is related to time. By controlling the linear speed and duration of shearing to make the total shear power within a certain range, the expected emulsification effect can be achieved to form a uniform emulsion.

[0035] In one embodiment, the viscosity of the emulsion formed after shearing in step (3) is 500-150000 mPa·s, including but not limited to 500 mPa·s, 5000 mPa·s, 10000 mPa·s, 30000 mPa·s, 50000 mPa·s, 70000 mPa·s, 90000 mPa·s, 100000 mPa·s, 110000 mPa·s, 130000 mPa·s, 150000 mPa·s or a range between any two of them.

[0036] In one embodiment, in the emulsion formed by mixing solution X and solution Y in step (3), in this system, bisphenol A oxygen anions can be continuously generated by the polycarbonate material through a hydrolysis reaction and migrated to the aqueous phase. Since the emulsion can maintain stability under the action of a sufficient amount of bisphenol A monomer, the hydrolysis reaction process of the polycarbonate can continue when the interfacial area is sufficient;

[0037] Specifically, the hydrolysis reaction has a temperature of 30-70°C and a time of 24-48h. Specifically, the temperature includes but is not limited to 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C or a range between any two of them, and the time includes but is not limited to 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h or a range between any two of them.

[0038] Specifically, the hydrolysis reaction maintains the reaction system pH=12-14, including but not limited to 12, 12.2, 12.5, 12.8, 13, 13.2, 13.5, 13.8, 14 or a range between any two thereof;

[0039] Preferably, during the hydrolysis reaction of the polycarbonate material, an alkali solution is added to maintain the pH of the system. The alkali in the alkali solution can refer to the optional range of the alkali added to the solution Y in step (2). The specific selection of the two can be the same or different. Specifically, the alkali solution is preferably a NaOH aqueous solution, for example, a NaOH aqueous solution with a mass concentration of 2-35%, preferably 15-20%.

[0040] In one embodiment, the emulsion formed after shearing in step (3) needs to be transferred to a reactor to stay and complete the hydrolysis reaction, and preferably a kettle reactor or a tubular reactor is used for the hydrolysis reaction;

[0041] In a specific example, the hydrolysis reaction can adopt a tank reactor, wherein the linear speed of the mixing and stirring paddle is preferably 0.5-5.0 m / s; in addition, the one-way residence time in the reactor is preferably 24-48 h; specifically, the linear speed includes but is not limited to 0.5 m / s, 1 m / s, 1.5 m / s, 2 m / s, 2.5 m / s, 3 m / s, 3.5 m / s, 4 m / s, 4.5 m / s, 5.0 m / s or a range between any two of them, and the one-way residence time includes but is not limited to 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h, 38 h, 40 h, 42 h, 44 h, 46 h, 48 h or a range between any two of them.

[0042] In one embodiment, the reaction solution after the one-way hydrolysis reaction in step (4) needs to be demulsified and separated to obtain an aqueous solution containing bisphenol A, wherein the bisphenol A exists in the form of a salt (such as BPA sodium salt) and has a relatively clean composition, does not contain impurities such as inorganic salts, and can be directly used in the interfacial phosgene method to synthesize polycarbonate;

[0043] The aqueous solution containing bisphenol A, wherein the content of bisphenol A can be measured by liquid phase method, preferably the content is 5-20wt%, and the rest is 70-90wt% of water and about 3-7wt% of alkali.

[0044] In the method described above in the present invention, after demulsification and separation in step (4), the oil phase is obtained at the same time, which mainly comprises organic solvent, components in the polycarbonate material that do not participate in the hydrolysis reaction, unhydrolyzed polycarbonate material and other components. The hydrolysis rate of the polycarbonate material that only undergoes a single-pass hydrolysis reaction is relatively low, usually less than 50%; therefore, the oil phase can be concentrated to remove the organic solvent, and the solvent removal rate can be controlled to obtain a concentrated solution with a polymer content of 10-30wt%, which is returned to step (1) to continue to participate in the preparation of solution X, and the cycle operation is repeated to improve the hydrolysis rate of the polycarbonate material; it should be noted that the concentrated solution with a polymer content of 10-30wt%, wherein the polymer includes the components in the polycarbonate material that do not participate in the hydrolysis reaction and the unhydrolyzed polycarbonate material, therefore, polycarbonate and the blended modified polymers that may be contained are all calculated. In one embodiment, the demulsification and separation in step (4) can be carried out by conventional operation methods in the field; preferably, the demulsification is carried out by filtration through a hydrophilic filter paper sheet, such as a fiber filter paper sheet with a pore size of 1-20 μm, specifically, the pore size includes but is not limited to 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm or a range between any two of them; preferably, the separation is carried out by centrifugation or a coalescer.

[0045] In the present invention, the aqueous solution containing bisphenol A obtained after the steps of hydrolysis / demulsification / separation has a BPA mass fraction of 5-20% and a pH of 12-14, and can be applied to the process of preparing polycarbonate by interfacial polycondensation.

[0046] At present, polycarbonate is prepared by interfacial polycondensation, which is one of the processes commonly used in industry. Its direct raw materials include about 15wt% BPA sodium salt solution, organic solvents such as dichloromethane, phosgene, catalyst triethylamine, end-capping agent and other raw materials. After mixing, rapid stirring is performed to increase interfacial renewal and mass transfer to achieve rapid polycondensation reaction to prepare high molecular weight polycarbonate materials. Therefore, the aqueous solution containing bisphenol A obtained by the present invention can be directly used or its concentration can be appropriately adjusted and directly used as a raw material for the preparation of interfacial polycondensation PC, without the need to re-purchase the corresponding powder raw materials for solution preparation, which can effectively reduce the cost of raw materials and the risk of dust in the device.

[0047] In one embodiment, the aqueous phase in step (3) is a solution containing bisphenol A. When used, the concentration and pH of bisphenol A in the solution are first analyzed, and then bisphenol A monomer and alkali solution are added to the required amount, and then the interfacial phosgene method is used to synthesize polycarbonate.

[0048] In the present invention, the bisphenol A solution obtained from the aqueous phase of step (3) can also be subsequently separated and purified to obtain bisphenol A monomer. The separation and purification process can be conventional methods such as crystallization and distillation. The specific operation and process conditions, and the devices used can all be selected conventionally in the art, and there is no particular limitation. The technicians can optimize the process based on the known process in the prior art according to actual needs, and the present invention will not repeat them.

[0049] Compared with the prior art, the positive effects of the present invention are:

[0050] The present invention provides a chemical method for reclaiming waste polycarbonate materials. The method is implemented in an emulsified system of a mixture of an organic solvent and water. In the emulsion state provided by the present invention, no additional catalyst and substances such as methanol need to be added, and the decomposition of the polycarbonate chain can be completed under mild conditions. In addition, the BPA salt solution obtained by decomposition is relatively pure and can be directly used in the interfacial polycondensation method to synthesize polycarbonate, saving costs and improving the economic efficiency of the device. DETAILED DESCRIPTION

[0051] The following will use more detailed specific examples to describe the process of promoting the hydrolysis of polycarbonate chains by shear emulsification under the conditions of a water-oil interface system. It should be noted that the present invention is not limited to the following examples.

[0052] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:

[0053] Polycarbonate material A: Wanhua 2600, Mw = 17456 g / mol, PD = 2.4, λ = 0.0067;

[0054] Polycarbonate material B: derived from recycled CD discs, Mw = 16735 g / mol, monomer composition includes about 94wt% bisphenol A and about 6wt% vinyl monomer;

[0055] Polycarbonate material C: derived from recycled PC transparent protective face shield, Mw=24566 g / mol, monomer composition includes about 96wt% of bisphenol A, and about 4wt% of styrene and other vinyl monomers;

[0056] Bisphenol A: analytical grade, Anergy;

[0057] Dichloromethane: analytical grade / chromatographic grade, Anergy;

[0058] NaOH: analytical grade, Anergy;

[0059] Deionized water: pH=7.2, conductivity<5.0.

[0060] The main analytical methods used in the examples and comparative examples of the present invention are:

[0061] Molecular weight of polycarbonate: obtained by Agilent Technologies 1260infinity test, using RI detector, UV detector, dichloromethane as mobile phase, flow rate of 1 mL / min, column temperature and box temperature are both 30°C.

[0062] The monomer content in the aqueous solution was analyzed by liquid chromatography using methanol as the eluent.

[0063] The monomer composition of polycarbonate materials B and C is H 1 -NMR was performed using deuterated dichloromethane as solvent and scanning was performed at a solution prepared at 4.0 mg / ml.

[0064] The emulsion viscosity test adopts Brookfield viscometer DV2T, 63# rotor, 35°C, rotation speed 1-20rpm, and reads the viscosity data in the state of stable fluctuation of torque range of 40-60%.

[0065] The polymer content in the oil phase is determined by an evaporation test. A certain mass m of organic solution is taken and an evaporation test is performed on an analytical balance. After evaporation to a stable mass, the balance reading is n, and the polymer content in the solution is n / m*100%.

[0066] The particle size of the crushed particles was characterized by using the German Synpatek dry particle size analyzer HELOS-RODOS. The test temperature was 25°C and the humidity was not higher than 80%. The particle diameter was expressed as D 3,2 Description, that is, area average particle size.

[0067] The test method for sodium carbonate and NaOH in the aqueous phase is carried out in accordance with standard GB / T4348.1-2013.

[0068] Example 1

[0069] (1) Prepare a 1L flask and crush the polycarbonate material A into pieces with a diameter of about D. 3,2 =0.08mm particles, take 100g and add thereto, continue to add 450g of dichloromethane solution, maintain a water bath at 30°C, wait for the polycarbonate material A to be completely dissolved to obtain solution X, filter it through a PTFE filter material with a pore size of 0.2μm, and seal it for use.

[0070] (2) Prepare a 1L flask, add 500g of deionized water, 0.1g of sodium thiosulfate, 5g of bisphenol A monomer, and then add 80g of 32wt% sodium hydroxide aqueous solution, maintain a 30°C water bath, and after the bisphenol A monomer is completely dissolved, obtain solution Y with a pH of 13.5 for standby use.

[0071] (3) Prepare a 1L beaker, add 241g of solution X and 337g of solution Y, insert a dynamic shear head below the liquid surface, control the speed to 10000rpm, and start emulsification at a linear speed of 7m / s. After 60s, the total shear power input reaches 0.6*10 6 J / m 3 A uniform and stable emulsion with a viscosity of 900cp is formed, which is then transferred to a 1L three-necked flask and subjected to hydrolysis at 35°C. The stirring linear velocity is controlled at 0.5m / s, and a 10wt% aqueous sodium hydroxide solution is added dropwise to the reaction system to maintain the pH value of the reaction system at 12-14. After the reaction is carried out for 24h, stirring is stopped.

[0072] (4) The reaction solution was demulsified by filtration through a fiber filter paper with a pore size of 1.0 μm, and an aqueous phase (i.e., an aqueous solution containing bisphenol A) was separated, with a pH of 12.5.

[0073] At the same time, an oil phase is obtained, which mainly contains dichloromethane and polymers (including monomer components in the polycarbonate material that do not participate in the hydrolysis reaction and unhydrolyzed polycarbonate material A).

[0074] The oil phase is used as a raw material, and after rotary evaporation concentration, the polymer concentration therein is made consistent with the initial concentration of the polycarbonate material A in the solution X in the above step (1), and the raw material ratio and operating parameters of the above steps (1)-(4) are repeated to cycle the hydrolysis reaction, and the mass of the polymer remaining in the oil phase separated after each reaction is tested respectively. At the same time, the water phase obtained after the cyclic hydrolysis reaction is combined with the previous one, and the total mass of BPA contained in the combined solution is tested successively.

[0075] After 5 cycles of hydrolysis of the above-mentioned 100g polycarbonate material A initial raw material, the total mass of the final aqueous phase combined liquid is 676.2g, which contains about 13.00wt% BPA monomer, 3.26wt% sodium hydroxide, 5.73wt% sodium carbonate, and the rest is water. The combined liquid can be directly used for the interfacial phosgene method to synthesize polycarbonate by adding bisphenol A monomer and alkali solution to the required amount.

[0076] The test results of the polymer content in the water phase and the oil phase after each separation are shown in Table 1 below.

[0077] Table 1

[0078] Number of hydrolysis reactions 0 1 2 3 4 5 Total BPA content in water phase (g) 5.0 29.9 54.1 67.4 81.1 87.9 Total mass of polymer in oil phase (g) 100.0 71.8 44.6 29.7 14.7 6.9

[0079] Example 2

[0080] (1) Prepare a 1L flask and crush the polycarbonate material B into pieces with a diameter of about D. 3,2 =0.21mm particles, take 150g and add it thereto, continue to add 450g of dichloromethane solution, maintain a water bath at 35°C, wait for the polycarbonate material B to be completely dissolved to obtain solution X, filter it through a PTFE filter material with a pore size of 4.0μm, and seal it for use.

[0081] (2) Prepare a 1L flask, add 500g of deionized water, 0.1g of sodium thiosulfate, 2g of bisphenol A monomer, and then add 40g of 32wt% sodium hydroxide aqueous solution, maintain a 30°C water bath, and after the bisphenol A monomer is completely dissolved, obtain solution Y with a pH of 13.0 for standby use.

[0082] (3) Prepare a 1L beaker, add 241g of solution X and 127g of solution Y, insert a dynamic shear head below the liquid surface, control the speed to 10000rpm, and start emulsification at a linear speed of 13m / s. After 60s, the total shear power input reaches 1.4*10 6 J / m 3 A uniform and stable emulsion with a viscosity of 7000cp was formed. Then it was transferred to a 1L three-necked flask and hydrolyzed at 45°C. The stirring line speed was controlled to be 2.4m / s. At the same time, 10wt% sodium hydroxide aqueous solution was added dropwise to the reaction system to maintain the pH of the reaction system at 12-14. After the reaction was carried out for 48h, stirring was stopped.

[0083] (4) The reaction solution was demulsified by filter pressing using a fiber filter paper with a pore size of 10 μm, and the aqueous phase (i.e., an aqueous solution containing bisphenol A) was separated, with a pH of 13.7.

[0084] At the same time, an oil phase is obtained, which mainly contains dichloromethane and polymer (including monomer components in the polycarbonate material that do not participate in the hydrolysis reaction and unhydrolyzed polycarbonate material B).

[0085] The oil phase is used as a raw material, and after rotary evaporation concentration, the polymer concentration therein is made consistent with the initial concentration of the polycarbonate material B in the solution X of step (1), and the raw material ratio and operating parameters of the above steps (1)-(4) are repeated to cycle the hydrolysis reaction, and the mass of the polymer remaining in the oil phase separated after each reaction is tested respectively. At the same time, the water phase obtained after the cyclic hydrolysis reaction is combined with the previous one, and the total mass of BPA contained in the combined solution is tested successively.

[0086] After 5 cycles of hydrolysis of the above-mentioned 150g polycarbonate material B initial raw material, the total mass of the final aqueous phase combined liquid is 707.4g, which contains about 17.90wt% BPA monomer, 5.35wt% sodium hydroxide, 8.00wt% sodium carbonate, and the rest is water. The combined liquid can be directly used for the interfacial phosgene method to synthesize polycarbonate by adding bisphenol A monomer and alkali solution to the required amount.

[0087] The test results of the polymer content in the water phase and the oil phase after each separation are shown in Table 2 below.

[0088] Table 2

[0089] Number of hydrolysis reactions 0 1 2 3 4 5 Total BPA content in water phase (g) 2.0 32.3 60.74 90.11 108.80 126.60 Total mass of polymer in oil phase (g) 150.0 115.6 83.7 50.8 29.8 9.2

[0090] Example 3

[0091] (1) Prepare a 1L flask and crush the polycarbonate material C into pieces with a diameter of about D. 3,2 =0.48mm particles, take 60g and add thereto, continue to add 450g of dichloromethane solution, maintain a water bath at 35°C, wait for the polycarbonate material C to be completely dissolved to obtain solution X, filter it through a PTFE filter material with a pore size of 9.0μm, and seal it for use.

[0092] (2) Prepare a 1L flask, add 500g of deionized water, 0.1g of sodium thiosulfate, 0.5g of bisphenol A monomer, and then add 100g of 32wt% sodium hydroxide aqueous solution, maintain a water bath at 30°C, and after the bisphenol A monomer is completely dissolved, obtain solution Y with a pH of 13.8 for use.

[0093] (3) Prepare a 1L beaker, add 180g of solution X and 180g of solution Y, insert a dynamic shear head below the liquid surface, control the speed to 10000rpm, and start emulsification at a linear speed of 20m / s. After 120s, the total input shear power reaches 2.9*10 6 J / m 3When the emulsion is stirred for 4 hours, a uniform and stable emulsion is formed with a viscosity of 14000cp. The emulsion is then transferred to a 1L three-necked flask and hydrolyzed at 55°C. The stirring line speed is controlled at 4.8m / s. At the same time, a 10wt% aqueous solution of sodium hydroxide is added dropwise to the reaction system to maintain the pH of the reaction system at 12-14. After the reaction is carried out for 48h, stirring is stopped.

[0094] (4) The reaction solution was demulsified by filter pressing using a fiber filter paper with a pore size of 15 μm, and an aqueous phase (i.e., an aqueous solution containing bisphenol A) was separated, with a pH of 13.4.

[0095] At the same time, an oil phase is obtained, which mainly contains dichloromethane and polymers (including monomer components in the polycarbonate material that do not participate in the hydrolysis reaction and unhydrolyzed polycarbonate material C).

[0096] The oil phase is used as a raw material, and after rotary evaporation concentration, the polymer concentration therein is made consistent with the initial concentration of the polycarbonate material C in the solution X of step (1), and the raw material ratio and operating parameters of the above steps (1)-(4) are repeated to cycle the hydrolysis reaction, and the mass of the remaining polymer in the organic oil phase separated after each reaction is tested respectively. At the same time, the water phase obtained after the cyclic hydrolysis reaction is combined with the previous one, and the total mass of BPA contained in the combined solution is tested successively.

[0097] After 5 cycles of hydrolysis of the above 60g polycarbonate material C initial raw material, the total mass of the final aqueous phase combined liquid is 656.6g, which contains about 7.80wt% BPA monomer, 2.26wt% sodium hydroxide, 3.59wt% sodium carbonate, and the rest is water. The combined liquid can be directly used for the interfacial phosgene method to synthesize polycarbonate by adding bisphenol A monomer and alkali solution to the required amount.

[0098] The test results of the monomers and polymers in the organic phase after each separation are shown in Table 3 below.

[0099] Table 3

[0100] Number of hydrolysis reactions 0 1 2 3 4 5 Total BPA content in water phase (g) 0.5 13.85 36.1 51.23 51.24 51.23 Total mass of polymer in organic phase (g) 60 44.8 18.9 2.8 2.9 2.8

[0101] Comparative Example 1

[0102] Referring to the method of Example 1, the only difference is that bisphenol A monomer is not added to solution Y in step 2), and other operations and conditions remain unchanged. After 5 cycles of hydrolysis, the total mass of the final aqueous phase combined liquid is 604.6 g, which contains about 3.68 wt % BPA monomer, 1.25 wt % sodium hydroxide, 1.71 wt % sodium carbonate, and the rest is water.

[0103] The test results of the polymer content in the water phase and the oil phase after each separation are shown in Table 4 below.

[0104] Table 4

[0105] Number of hydrolysis reactions 0 1 2 3 4 5 Total BPA content in water phase (g) 0 4.45 7.12 14.24 21.36 22.25 Total mass of polymer in oil phase (g) 100.0 94.8 91.7 83.6 75.6 75.3

[0106] Comparative Example 2

[0107] The method of Example 1 is referred to, except that: bisphenol A monomer is not added to solution Y in step 2), and the shear emulsification process is omitted in step 3), and solution X and solution Y are directly transferred into the reactor for hydrolysis reaction after mixing, and other operations and conditions remain unchanged. After 5 cycles of hydrolysis, the total mass of the final aqueous phase combined liquid is 587.9 g, which contains about 1.30 wt % of BPA monomer, 1.34 wt % of sodium hydroxide, 0.56 wt % of sodium carbonate, and the rest is water.

[0108] The test results of the polymer content in the water phase and the oil phase after each separation are shown in Table 4 below.

[0109] Table 4

[0110] Number of hydrolysis reactions 0 1 2 3 4 5 Total BPA content in water phase (g) 0 2.28 3.56 4.45 5.84 7.63 Total mass of polymer in oil phase (g) 100.0 97.2 96.2 95.5 93.5 91.3

Claims

1. A method for recovering bisphenol A by hydrolysis of polycarbonate, characterized in that: The following steps are included: (1) dissolving a polycarbonate material in an organic solvent to obtain a solution X; (2) mixing bisphenol A monomer, alkali and water to obtain solution Y; (3) mixing solution X and solution Y, obtaining a uniform emulsion through shearing, and transferring the mixture into a reactor for hydrolysis reaction; (4) The reaction liquid is demulsified and separated to obtain a water phase and an oil phase, respectively, wherein the water phase is an aqueous solution containing bisphenol A.

2. The method according to claim 1, characterized in that: The polycarbonate material in step (1) is selected from a polymer containing bisphenol A carbonate structural units in the molecular chain, preferably a polymer containing only bisphenol A carbonate structural units in the molecular chain; Preferably, the molecular chain refers to the main chain; and / or The average molecular weight of the polycarbonate material in step (1) is 2000-40000 g / mol.

3. The method according to claim 1, characterized in that In the solution X of step (1), the mass percentage of polycarbonate material is 10-30%; and / or The organic solvent in step (1) is a polar solvent, preferably a chlorine-containing organic solvent, more preferably one or more of dichloromethane and chlorobenzene; and / or The dissolving in step (1) is performed at a temperature of 24-38° C.; and / or The polycarbonate material in step (1) is crushed into particles with a diameter not exceeding 1 mm, preferably 0.05-0.5 mm; and / or In step (1), the solution X is filtered, and the pore size of the filter material used for filtering is less than 10 μm, preferably 0.5-7 μm.

4. The method according to claim 1, characterized in that: In the solution Y of step (2), the mass percentage of bisphenol A monomer is 0.05-1.5%, and the mass percentage of alkali is 2-8%; Preferably, the solution Y is strongly alkaline, with a pH of 12-14; and / or The mixing in step (2) is performed at a temperature of 25-35°C.

5. The method according to claim 1, characterized in that The base in step (2) is an inorganic base, preferably a hydroxide, more preferably one or more of an alkali metal hydroxide, an alkaline earth metal hydroxide, a tetraalkylammonium hydroxide, and ammonium hydroxide; Further preferably, the base is selected from alkali metal hydroxides, such as one or more of NaOH and KOH.

6. The method according to claim 1, characterized in that The solution Y of step (2) is added with a reducing agent, wherein the content of the reducing agent in the system is 50-500 ppm; Preferably, the reducing agent is selected from one or more of sodium or potassium sulfides and sulfites, preferably sodium thiosulfate.

7. The method according to claim 1, characterized in that The mass ratio of the solution X to the solution Y in step (3) is 0.5-5.0, preferably 0.5-2.0; and / or The shearing process in step (3) is performed at a linear speed of 2-20 m / s; Preferably, the total shear power of the shear process system is 0.5-3.0*10 6 J / m 3 ; and / or The emulsion in step (3) has a viscosity of 500-150000 mPa·s.

8. The method according to claim 1, characterized in that The hydrolysis reaction in step (3) is carried out at a temperature of 30-70° C. and a time of 24-48 h; Preferably, the hydrolysis reaction process maintains the reaction system pH = 12-14; Preferably, a kettle reactor or a tubular reactor is used for the hydrolysis reaction; more preferably, the hydrolysis reaction is carried out in a kettle reactor, wherein the linear velocity of the mixing and stirring paddle is preferably 0.5-5.0 m / s; and the one-way residence time in the reactor is preferably 24-48 h.

9. The method according to claim 1, characterized in that: The oil phase in step (4) is concentrated to remove the organic solvent to obtain a concentrated solution with a polymer content of 10-30 wt%, which is returned to step (1) to continue to participate in the preparation of solution X.

10. The method according to claim 1, characterized in that The aqueous solution containing bisphenol A is used for interfacial polycondensation to prepare polycarbonate.

Citation Information

Patent Citations

  • Chemical recovery method for waste polycarbonate material

    CN101407450A

  • Preparation method of polycarbonate

    CN106478934A

  • Method for catalyzing methanol alcoholysis of polycarbonate material to recycle bisphenol A with CaO-SBA-15 molecular sieve

    CN106748665A

  • New decomposing method for polycarbonate

    JP2009108101A

  • Method for Obtaining Bisphenol-A (BPA) from Polycarbonate Waste Using Microwave Radiation

    US20160185696A1